CLEANED WATER QUALITY IN THE EXPERIMENTAL CIRCUIT LABORATORY - Grisone, Agnese; Teirumnieks, Edmunds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
For the moment there is no problem, because the clean water complies with the following requirements. But it is the nature of the mechanical problems, where technical and cleaned water in the production process increased conductivity indicators and the pH value is less than the soft water after legislative dossier. Materials and methods are described in the clean water sampling physical – chemical testing, as well as describes the methods used. And you are prompted to create the electricity supply system, which, in addition to the accidental or unplanned power off position. It will depend on the results of a number of indicators. You can view a version of the technology, if not improving, the ability to create an automatic power supply system.